Relapses and disability accumulation in progressive multiple sclerosis - Paz Soldán, M Mateo; Novotna, Martina; Abou Zeid, Nuhad; Kale, Nilufer; Tutuncu, Melih; Crusan, Daniel J; Atkinson, Elizabeth J; Siva, Aksel; Keegan, B Mark; Pirko, Istvan; Pittock, Sean J; Lucchinetti, Claudia F; et al. (Neurology, 2015)
OBJECTIVE: We examined the effect of relapses-before and after progression onset-on the rate of postprogression disability accrual in a progressive multiple sclerosis (MS) cohort. METHODS: We studied patients with primary progressive MS (n = 322) and bout-onset progressive MS (BOPMS) including single-attack progressive MS (n = 112) and secondary progressive MS (n = 421). The effect of relapses on time to Expanded Disability Status Scale (EDSS) score of 6 was studied using multivariate Cox regression analysis (sex, age at progression, and immunomodulation modeled as covariates). Kaplan-Meier analysis was performed using EDSS 6 as endpoint. RESULTS: Preprogression relapses (hazard ratio [HR]: 1.63; 95% confidence interval [CI]: 1.34-1.98), postprogression relapses (HR: 1.37; 95% CI: 1.11-1.70), female sex (HR: 1.19; 95% CI: 1.00-1.43), and progression onset after age 50 years (HR: 1.47; 95% CI: 1.21-1.78) were associated with shorter time to EDSS 6. Postprogression relapses occurred in 29.5% of secondary progressive MS, 10.7% of single-attack progressive MS, and 3.1% of primary progressive MS. Most occurred within 5 years (91.6%) after progressive disease onset and/or before age 55 (95.2%). Immunomodulation after onset of progressive disease course (HR: 0.64; 95% CI: 0.52-0.78) seemingly lengthened time to EDSS 6 (for BOPMS with ongoing relapses) when analyzed as a dichotomous variable, but not as a time-dependent variable. CONCLUSIONS: Pre- and postprogression relapses accelerate time to severe disability in progressive MS. Continuing immunomodulation for 5 years after the onset of progressive disease or until 55 years of age may be reasonable to consider in patients with BOPMS who have ongoing relapses.
Keywords: výsledek terapie; Recurrence; proporcionální rizikové modely; Young Adult; Disability Evaluation; Immunologic Factors; Male; progrese nemoci; mladý dospělý; posuzování pracovní neschopnosti; chronicko-progresivní roztroušená skleróza; Kaplan-Meier Estimate; Proportional Hazards Models; Adult; Kaplanův-Meierův odhad; dospělí; mužské pohlaví; Disease Progression; Multiple Sclerosis, Chronic Progressive; recidiva; Severity of Illness Index; Treatment Outcome; Multivariate Analysis; lidé; ženské pohlaví; Humans; stupeň závažnosti nemoci; imunologické faktory; multivariační analýza; Female; lidé středního věku; Middle Aged